Bridging Strategy from Both Business Economics and Design Sciences - Jörn Bühring; Brigitte Borja de Mozota; Patricia A. Moore (Cubic Journal, 2023)
Consensus on the impact of design on perfor-mance can be said to be evident at all three levels of decision-making in organizations: strategic, tac-tical, operational (Brunswicker et al. 2019; Gemser & Leenders 2001). This impact broadly assumes the following forms: